Performance Evaluation of Co-Operative Banks of Telangana – An Empirical Study: Examining Risk Management Practices and Performance of Co-operative Banks in Telangana (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The Co-operative Banks of Telangana approach to risk management is examined in this article.As a result of the ever-changing nature of the market, the growth of technology, the shifting wants ofconsumers, and other factors, banks in the contemporary period are forced to deal with several financialcrises and issues. Banking in India has been around for more than two centuries. In 1786, it began itstrip. After the nationalization of banks in 1969, the industry underwent a major transformation. Theliberalization, privatization, and globalization policies of the government aided the fast growth of thisbusiness. From lending and purchasing to other financial amenities, banking liberalization and economicreforms in India opened up various avenues for the banks. Because of this, banks began to see severalbeneficial developments and subsequent growth. This was a significant development in the Indianfinancial landscape. The cooperative bank's most pressing worry is the growing volume of nonperformingassets (NPAs) (NPAs). The entire risk exposure associated with banking operationsnecessitates a systematic risk management approach. Co-operative Banks in India were examined in thisresearch for their risk management practices. This research relied on secondary data.